The effects of cupping massage in reducing competitive anxiety in athletes - ouali, abdennour (sports creativity, 2025)
The phenomenon of cupping has spread among several athletes in many international sports , several studies have emerged that deal with some of the effects of its different types. On the contrary, we find a lack of studies of it in the Algeria and the scarcity of its use between Algerian athletes, as the study aimed to know the effect of using cupping massage to reduce the anxiety of sporting competition For volleyball players, for this reason , a sample was deliberately chosen that included 16 players divided into two groups, with 8 players for each group, to depend on the experimental approach in the two groups' equivalence method, as a result the study concluded that the use of massage by cupping leads to a reduction of anxiety sporting competition, leading the player to be better in their performance